2018
DOI: 10.1161/jaha.117.008257
|View full text |Cite
|
Sign up to set email alerts
|

IL‐23R Deficiency Does Not Impact Atherosclerotic Plaque Development in Mice

Abstract: BackgroundInterleukin‐23 (IL‐23) has been implicated in inflammatory and autoimmune diseases by skewing CD4+ T helper cells towards a pathogenic Th17 phenotype. In this study we investigated the presence of IL‐23 receptor (IL‐23R)‐expressing cells in the atherosclerotic aorta and evaluated the effect of IL‐23R deficiency on atherosclerosis development in mice.Methods and ResultsWe used heterozygous Ldlr −/− Il23r e GFP / WT knock‐in mice to identify IL‐23R‐expressing cells by flow cytometry and homozygous Ldlr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Just as Table 4. Although IL-12 family Fairweather et al, 2003;Yang et al, 2011;Nyland et al, 2012;Jenke et al, 2014;Kong et al, 2014;Hu et al, 2014;Zha et al, 2015;Zhang et al, 2017;Miteva et al, 2017;Sesti-Costa et al, 2017;Ouyang et al, 2017;Xu et al, 2018 Zhou et al, 2001;Kempe et al, 2009;Correia et al, 2010;Lin et al, 2012;Khojasteh-Fard et al, 2012;Jin et al, 2012;Yong et al, 2013;Chistiakov et al, 2015;Abbas et al, 2015;A Shahi et al, 2015;Zykov et al, 2016;Opstad et al, 2016;Zhu et al, 2018;Rasa et al, 2018; Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Subramanian et al, 2015;Kan et al, 2016;Tao et al, 2016;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Ryu et al, 2018;Huang et al, 2019;Huang et al, 2019;Wang et al, 2019;Jia et...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Just as Table 4. Although IL-12 family Fairweather et al, 2003;Yang et al, 2011;Nyland et al, 2012;Jenke et al, 2014;Kong et al, 2014;Hu et al, 2014;Zha et al, 2015;Zhang et al, 2017;Miteva et al, 2017;Sesti-Costa et al, 2017;Ouyang et al, 2017;Xu et al, 2018 Zhou et al, 2001;Kempe et al, 2009;Correia et al, 2010;Lin et al, 2012;Khojasteh-Fard et al, 2012;Jin et al, 2012;Yong et al, 2013;Chistiakov et al, 2015;Abbas et al, 2015;A Shahi et al, 2015;Zykov et al, 2016;Opstad et al, 2016;Zhu et al, 2018;Rasa et al, 2018; Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Subramanian et al, 2015;Kan et al, 2016;Tao et al, 2016;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Ryu et al, 2018;Huang et al, 2019;Huang et al, 2019;Wang et al, 2019;Jia et...…”
Section: Resultsmentioning
confidence: 99%
“…Therapy involving IL-23p19, a subunit of IL-23, had no significant effect on atherosclerosis development in ApoE-deficient mice, although inflammatory responses were reduced . Another study reported that there was no significant difference in atherosclerotic area between low-density lipoprotein receptor (LDLR) knockout mice and IL-23 + LDLR double-knockout mice, after they were all fed with high-fat diet (Engelbertsen et al, 2018). A recent study reported that deficiency of IL-23 significantly decreased IL-22 expression in ApoE-knockout mice, and also reduced expression of IL-22, thereby relieving the release of inflammatory substances, and thus alleviating the process of atherosclerosis (Fatkhullina et al, 2018).…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, systemic expression of IL-23 in a transgenic model induced an inflammatory phenotype and promoted various inflammatory diseases, predisposing to atherosclerosis (Wiekowski et al, 2001). Short-term IL-23 injections have been shown to increase apoptosis in plaques, likely acting in a GM-CSF dependent manner, and it was shown that early lesions could develop unperturbed in the absence of IL-23R (Engelbertsen et al, 2018; Subramanian et al, 2015). In our model genetic inactivation of IL-23 resulted in an increased number of apoptotic cells in atherosclerotic plaques, confirming that apoptosis in the plaque is tightly linked to atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%